Pengharaman Khamr dalam Al-Qur’an: Analisis Sosio-Historis dan Tantangannya di Masyarakat Muslim Kontemporer - Ikhsan Kamil; Kiki Muhamad Hakiki; Ahmad Muttaqin (Studia Quranika, 2026)
Khamr, or intoxicating beverages, has long been a social issue of concern in Islamic teachings, particularly due to its impact on individuals and society. Although the Qur’an explicitly prohibits khamr, questions remain regarding the socio-historical background behind its prohibition. Therefore, this study aims to analyze the underlying factors of khamr prohibition in the Qur’an through a socio-historical approach and to examine the interpretation of relevant verses according to the commentaries of At-Thabari and Ibn Kathir. This research employs a library research method by utilizing primary sources such as the Qur’an, classical exegesis, and other relevant literature. The findings reveal that the prohibition of khamr was not only based on religious principles but also closely related to the social conditions of Arab society during the time of Prophet Muhammad (PBUH), in which the consumption of khamr caused intellectual decline, social conflict, and disharmony in community life. The interpretations by At-Thabari and Ibn Kathir emphasize that although khamr may have limited benefits, its harms far outweigh them in terms of physical, moral, and social aspects.